What is a musical sign?: A guess at the riddle - Dougherty, William P. (Interdisciplinary Studies in Musicology, 2014)
Issues surrounding the nature of the musical sign loom large in the development of a viable musical semeiotic that goes beyond ad hoc or impressionistic appropriations of terminology. This article articulates an understanding of the sign with specific relevance to the analysis of musical topics by rigorously applying Peirce’s semeiotic theory to illuminate the nature of sign functioning in music.